Waste separation at source behaviour among Malaysian households: The Theory of Planned Behaviour with moral norm - Fitriyah, Razali; Dzurllkanian, Daud; Choong, Weng Wai; Wilson Rangga, Anthony Jiram (Elsevier Science, Ltd., 2020)
Background Malaysia, as one of the countries that intend to achieve the 17 Sustainable Development Goals (SDGs) by the United Nations (UN). Under the responsible consumption and production goals category, Malaysian households should take part by practising waste separation at home when the Separation at Source Initiative (SSI) under Solid Waste and Public Cleansing Management Act 2007 (Act 672) launched and effective in September 2015. However, many households in Malaysia is unwilling to participate. As the local authority has taken an extrinsic motivation thru SSI, this paper will study the impact of intrinsic motivation among the households. This paper purpose is to emphasise the part of intrinsic motivation thru extended Theory of Planned Behaviour in influencing households waste separation behaviour. A questionnaire survey was conducted towards high-rise residential units in Kuala Lumpur, Malaysia and obtained a total of 900 valid questionnaires. Data are analysed using the Smart PLS software. The results show that all the determinants from the model that consists of attitude towards behaviour, subjective norm, perceived behaviour control, and moral norm are significant. All the determinants positively influence the waste separation behaviour with the moral norm as the most influential determinant in improving households intrinsic motivation to engage with the waste separation at source behaviour. This paper result with the suggestions to foster waste separation behaviour among households based on the findings.